COURSE FEATURES OF PEDIATRIC RENAL MICROLITHIASIS AND OXIDATIVE STRESS IN CHILDREN - Lembryk, I.S.; Volosianko, A.B.; Tsytsiura, O.O.; Shlimkevych, I.V.; Zhyliak, O.V.; Buiak, P.Z.; Stefanyshyn, A.B. (World of Medicine and Biology, 2022)
Oxidative stress plays a major role in the development of metabolic renal diseases in children. We established the pediatric renal microlithiasis course in the setting of disorders of lipid peroxidation. 176 children aged 1 to 18 years were examined who were diagnosed with renal microlithiasis and were out-patients and in-patients in the Regional Children Counselling Outpatient Clinic and Nephrology Department of the Public Nonprofit Enterprise “Ivano-Frankivsk Regional Children`s Clinical Hospital of Ivano-Frankivsk Oblast Council” during the period of 2016 till 2019. Most commonly, in children the diagnosis of oxaluria (34.1 %) and oxalate-calcium nephropathy (30.1 %) was verified. Based on gender, girls prevail over boys (75.0 % and 25.0 %, р
Keywords: disease progression; children; nephrolithiasis; kidney calculi; oxidative stress; diagnosis